2019
DOI: 10.1111/febs.15020
|View full text |Cite
|
Sign up to set email alerts
|

Dracorhodin perchlorate protects pancreatic β‐cells against glucotoxicity‐ or lipotoxicity‐induced dysfunction and apoptosis in vitro and in vivo

Abstract: Glucotoxicity or lipotoxicity leads to hyperglycemia and insulin secretion deficiency, which are important causes for the onset of type 2 diabetes mellitus (T2DM). Thus, the restoration of β‐cell function is a long‐sought goal in diabetes research. Previous studies have implicated pancreatic and duodenal homeobox 1 gene (Pdx1) in β‐cell function and insulin secretion. In this study, we established a Pdx1 promoter‐dependent luciferase system and identified the natural compound dracorhodin perchlorate (DP) as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Glucotoxicity and lipotoxicity are among the main reasons leading to insufficient pancreatic βcell mass and β-cell dysfunction in T2DM (33,49). Besides, those conditions are associated with the downregulation of PDX1 in β-cells (17,50). Our analyses revealed that under both normal and toxic glycolipid conditions in vitro, TG might promote PDX1 expression and exert significant protective effects on islet β-cells against apoptosis by stimulating the ERK signaling.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Glucotoxicity and lipotoxicity are among the main reasons leading to insufficient pancreatic βcell mass and β-cell dysfunction in T2DM (33,49). Besides, those conditions are associated with the downregulation of PDX1 in β-cells (17,50). Our analyses revealed that under both normal and toxic glycolipid conditions in vitro, TG might promote PDX1 expression and exert significant protective effects on islet β-cells against apoptosis by stimulating the ERK signaling.…”
Section: Discussionmentioning
confidence: 72%
“…Currently, there are only limited drugs available that can protect islet β-cells and treat diabetes. PDX1 is an important anti-diabetes drug target (17,47), which has a vital role in maintaining islet β-cell function and survival (48). Herein, we reported that TG, a natural compound, could promote the expression of PDX1 in islet β-cells, and effectively prevent and rescue β-cells from glucotoxicity and lipotoxicity in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations